THE EFFECTS OF ECLECTIC TEACHING APPROACH IN MATHEMATICS FOR GRADE IX STUDENTS - Delgado, June Venelee A; Villaganas, Victor D (Journal of Agriculture and Technology Management, 2015)
The study assessed the performance level of Grade IX students in Mathematics after being exposed to conventional teaching approach (CTA) and the eclectic teaching approach (ETA) at Mandaue City Comprehensive National High School during the School Year 2014–2015. This study aimed to compare the effectiveness of CTA and ETA based on the students’ performance level before and after they were exposed to these strategies in the fourth grading period, using their Pre test-Post test scores. Results of the study showed that the performance of students (Section A) exposed to the Conventional Teaching Approach and those students (Section B) exposed to the Modular Teaching Approach were both low in the pre-test, but showed minimal improvement in the post-test. There was a significant pre-post mean increase of the students’ performance in Mathematics IX using both CTA and ETA. Moreover, there was no significant difference on the mean increase between the students’ performance using these aforementioned approaches of teaching, which proved that the effectiveness of these approaches were comparable. The findings indicate that ETA can be an alternative way to CTA.